Efficacy of pharmacological treatment for closure of patent ductus arteriosus in preterm newborns: a systematic review - Cerquin Sangay, Mario Alberto; Bazualdo Fiorini, Enzo Renatto; Bueno Ordóñez, Segundo (Salud Integral y Comunitaria, 2026)
Introduction: Patent ductus arteriosus (PDA) represents a relevant clinical problem due to its hemodynamic implications, especially in premature newborns, which has motivated multiple studies on its management. Currently, pharmacological treatment is one way to solve this problem, but there is no clear consensus as to which treatment is the most effective and least risky. Objective: The aim of this study was to find the drug with the highest rate of efficacy in PDA closure and with the least adverse effects. Methods: A descriptive systematic review was carried out following PRISMA guidelines. The search was carried out in SCOPUS, PUBMED, SCIELO, COCHRANE and LILACS databases. Results: After applying certain inclusion criteria, we obtained a total of 20 studies, most of which were systematic reviews and cohort studies. Among the studies reviewed, drugs such as indomethacin, ibuprofen, paracetamol and betamethasone have been used, finding that among the first three there is no statistically significant difference in efficacy. Closure rates and adverse effects vary considerably in the different studies, depending on factors such as dose, route of administration and gestational age of the neonate. Conclusions: The studies reviewed show that both ibuprofen and indomethacin have similar efficacy in PDA closure in preterm infants. Indomethacin is associated with higher risks of adverse effects. Acetaminophen appears to be a safe and effective alternative, with a superior safety profile compared to NSAIDs.